Topical and intradermal delivery of PpIX precursors for photodynamic therapy with intense pulsed light on porcine skin model - Requena, Michelle Barreto; Vollet Filho, José Dirceu [UNESP]; Barboza de Nardi, Andrigo [UNESP]; Escobar, Andre [UNESP]; da Rocha Adams, Rozana [UNESP]; Bagnato, Vanderlei Salvador; de Menezes, Priscila Fernanda Campos (Springer Nature, 2019)
In order to purposely decrease the time of the photodynamic therapy (PDT) sessions, this study evaluated the effects of PDT using topical and intradermal delivery of two protoporphyrin (PpIX) precursors with intense pulsed light (IPL) as irradiation source. This study was performed on porcine skin model, using an IPL commercial device (Intense Pulse Light, HKS801). IPL effect on different administration methods of two PpIX precursors (ALA and MAL) was investigated: a topical cream application and an intradermal application using a needle-free, high-pressure injection system. Fluorescence investigation showed that PpIX distribution by needle-free injection was more homogeneous than that by cream, suggesting that a shorter drug-light interval in PDT protocols is possible. The damage induced by IPL-PDT assessed by histological analysis mostly shows modifications in collagens fibers and inflammation signals, both expected for PDT. This study suggested an alternative protocol for the PDT treatment, possibility half of the incubation time and with just 3 min of irradiation, making the IPL-PDT, even more, promising for the clinical treatment.
Keywords: Aminolevulinic acid; Intense pulsed light; Methyl aminolevulinate; Photodynamic therapy; Porcine skin